P-41 What the men say: men's space: developing a group for men, run by men. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - Popplestone-Helm, Sarah; Jackson, Matt
Abstract : Engaging in group work is challenging. Men with a palliative diagnosis can be reticent to accept group support. This abstract introduces a group of men with a palliative diagnosis who want to tell their story. The group meets at their local hospice's, 'Men's Space'. It was slow to start but they developed a close bond, an ethos of care, support and a sense of fun. They wanted to break down barriers and expel myths to encourage other men to join. The group planned and held a day to encourage new members. As numbers grew, they engaged in gardening, painting and other activities. They welcomed speakers including a Para-Olympian. Supported by the family support and hospice nursing teams they toured local factories, met with a premiership rugby team and a National League basket-ball team. They are currently engaged in developing a calendar of their experiences together to raise funds for the hospice. Local businesses provided them with a summer house to meet in, and a greenhouse in which they produce vegetables for the hospice kitchen, for themselves and their families. It is difficult when group members die, but the group has developed ways of remembering each other, they talk openly about what they want from each other as their own deaths approach. This self-directed group is passionate and articulate, willing to speak at national level to ensure longevity for the men who come after them. They have made videos for the hospice website. Met with the local commissioning group and talked to external hospital groups to encourage others to join Men's Space or to set up something similar. What the men say: ' I love to sit and listen to the banter around the table .' ' It gives me the confidence to keep going when things are looking bleak .'